Pirates of the Philippines: A Critical Thinking Exercise - Macaraeg, Ruel A. (Revista de Artes Marciales Asiáticas, 2012)
Piracy had a formative impact on Filipino history, yet modern practitioners of Filipino Martial Arts generally do not acknowledge its influence. This brief study reconstructs the pirates’ martial practices through comparative historical analysis of their weapons, costume, and organization in order to draw conclusions about their relationship to martial cultures in the Philippines and across the region. Using analogous historical studies on piracy worldwide and examination of traditional arms and armor, this article restores the Iranun pirates to their rightful place as primary contributors to Filipino fighting arts and their influence in shaping Filipino national historiography as a whole.